The Effect of Hopping Training on the Lay-Up Shooting Ability of Basketball Games in Extracurricular SMA Negeri 1 Tebing Tinggi, Empat Lawang - Syahrianto, Syahrianto; Lian, Bukman; Junaidi, Ilham Arvan (Journal of Social Work and Science Education, 2023)
According to the researchers’ observations of the students of SMA Negeri 1 Tebing Tinggi Empat Lawang Regency, there have not been seen students who really have good lay-up shoot techniques, one of the weak points is the low initial technique carried out, then the lack of jumping ability and weak legs or knee joints when landing after shooting, so that this greatly affects his playing ability. Therefore, the purpose of this study is to determine the effect of hopping training on the lay-up shooting ability of basketball games in extracurricular SMA Negeri 1 Tebing Tinggi Empat Lawang Regency as well as provide solutions to solve the problem. The method used in this study was an experimental method with the subject of the study being students of SMA Negeri 1 Tebing Tinggi Kabupaten Empat Lawang who participated in extracurricular activities of basketball games with a total of 30 students. The data collection technique is based on the results of the initial test and the final test, with the test instrument being a shooting lay-up of a basketball game for 30 seconds. Based on the results of research conducted by researchers on students of SMA Negeri 1 Tebing Tinggi Empat Lawang Regency, the results of the calculation were 20.66. This value when consulted with the distribution table t with a sample number of 30 students, namely the value of t-table is 2.75. It has become a stipulation that if the calculation > t-table, the research has an influence, so that thus it can be concluded that there is an effect of hopping training on the lay-up shooting ability of basketball games in extracurricular SMA Negeri 1 Tebing Tinggi Empat Lawang Regency.